Um olhar sobre as contribuições dos meios tecnológicos dentro do processo de gestão democrática e participativa na educação - Iezzi, Denise Viola Dalpino (Universidade Federal de São Carlos, 2021)
This study aimed to better understand the functioning of the schools surveyed regarding democratic and participatory management from the perspective of technological means as factors that can contribute to this process. Against the background of the School Council and APM as a very important social function that instrumentalize and guarantee the exercise of democracy by participants in actions in schools, it was necessary to research which paths have been the most used for the construction of these actions in schools, analyzing and reflecting on the situation in which they find themselves. In this context, the COVID-19 pandemic has caused great impacts on education and the main one is the absence of presence in schools. As a result, the face-to-face meetings of the School Council and APM did not happen or did not happen very much. We use a methodological approach with a qualitative focus and for data collection, where we use a questionnaire, interview, and observation, with a participant-research strategy. The research was carried out in two Municipal Schools of Basic Education (EMEBs) in the city of Batatais - SP, which belong to a total of seven municipal schools that attend Kindergarten and Elementary School. And as participants, we had a director, a coordinator, two teachers, two employees and two parents, in each of the 2 schools surveyed, totaling 16 participants. In the analyses, we realized the importance that the development of a democratic and participative school management brings when built with collective participation and that helps in the construction of knowledge and knowledge of the school reality, following the path of transformation and democracy in education. Thus, we consider that the introduction and use of technological means for communication and interaction between participants could be used in order to continue the actions remotely, since previously the meetings were held in person and, in this way, even more necessary as a facilitating and functional means within school environments. Finally, regarding the results obtained, we noticed a great tendency on the part of the subjects to put these procedures into practice, considering the role of the director of fundamental importance for this, as he is the main driver of this process.
A look at the contributions of technological media inside the process of democratic and participatory management in education
Una mirada a las contribuciones de los medios tecnológicos dentro del proceso de gestión democrática y participativa en educación
Keywords: Gestão democrática; Ferramentas tecnológicas; Coletividade; Reuniões; Comunicação; Democratic management; Technological tools; Collectivity; Meetings; Communication; CIENCIAS HUMANAS::EDUCACAO